The rare histological forms of gallbladder cancer - Lytvynenko, M. V.; Rosha, L. G.; Chetverykov, S. G.; Vododuk, V. U.; Sherstiuk, S. A.; Katsap, A. V. (Морфологія / Morphologia / Morfologìâ, 2011)
In the practice of surgeons meet the rare forms of gallbladder cancer, with atypical clinical course. The aim of our investigation was revealed peculiarity of clinical display the rarely forms of gallbladder cancer. According to literature squamous cell carcinoma found in the gallbladder in 7% case.